Crisis-handling patterns: A multi-case study in Indonesia - Rosalina, Indah Fajar; Sari, Wina Puspita; Putriana, Muria; El Farabi, Qoryna Noer Seyma; Soegiarto, Asep; Salsabil, Ghina Balqis; Akhsan, Rivanda Kamil (Priviet Social Sciences Journal, 2025)
This study examines crisis communication patterns in cross-sector organizations in Indonesia through case studies of GenFM, PT KAI Commuter, and KitaBisa. GenFM faced a reputational crisis following an on-air joke by a radio host that violated broadcasting ethics, KAI Commuter experienced a security breach of its Multi-Trip Card system that caused financial and reputational damage, and KitaBisa dealt with public allegations of non-transparent donation management. Using a descriptive qualitative approach and guided by Situational Crisis Communication Theory (SCCT), this research analyzes the types of crises, public attribution of responsibility, and communication strategies employed by each organization. Data were collected through in-depth interviews, observations, and secondary document analysis. The findings show that the three organizations adopted distinct communication patterns: KitaBisa emphasized transparency and empathy to restore trust; GenFM prioritized swift clarification and professionalism; and KAI Commuter implemented systematic, collaborative, and technically driven responses. All three rely heavily on digital platforms as primary communication channels. The study highlights that the effectiveness of crisis communication is determined by the alignment between strategies and the nature of the crisis, as well as the organization’s openness to addressing public concerns.